Resource-Sharing Queueing Systems with Fluid-Flow Traffic - Mahabhashyam, Sai Rajesh; Gautam, Natarajan; Kumara, Soundar R. T. (Operations Research, 2008)
A system consisting of two buffers, each with independent fluid sources, is considered in this paper. Due to ease of implementation, the output capacities for the two buffers depend on the workload of only one of the buffers that is measured. A threshold-based policy is considered to dynamically assign output capacities for both buffers. Marginal workload distributions for the two buffers need to be evaluated for this policy. The key contribution of this paper is the performance analysis to derive the workload distribution in the two buffers. In addition, the paper also provides some guidelines to choose the output capacities for the two buffers as well as a mathematical program to determine an optimal threshold to dynamically switch between output capacities. Further, various applications of such systems to computer-communication networks are discussed.